2014
DOI: 10.1097/scs.0b013e3182a75102
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Synostoses of Uninvolved Sutures After Surgical Treatment of Nonsyndromic Craniosynostosis

Abstract: Management of craniosynostosis has evolved over time with increasing availability of effective and safe treatments. During long-term follow-up, a small number of patients may develop premature closure of a different suture that did not undergo surgical manipulation. In our case, series, we identified 3 patients undergoing open surgery and 2 patients undergoing endoscopic surgery for nonsyndromic, single-suture craniosynostosis. This finding supports the necessity of long-term clinical follow-up and the utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…13 Finally, a recent study from our group found similar rates of delayed synostosis of uninvolved sutures between open and endoscopic procedures in non-syndromic patients. 35 …”
Section: Discussionmentioning
confidence: 99%
“…13 Finally, a recent study from our group found similar rates of delayed synostosis of uninvolved sutures between open and endoscopic procedures in non-syndromic patients. 35 …”
Section: Discussionmentioning
confidence: 99%
“…34,38,39 The incidence of raised ICP following primary surgical correction in single-suture SC ranges widely from 1.5% to 44% 1,2,5,29,34,35,40,41 and adjacent synostoses occur following both ES 17,44 and CVR. 5,9,44 The addition of a syndromic diagnosis further increases the risk of restenosis and raised ICP. 9,43 Based on the present study and current literature, it is not clear whether ES or CVR are equivalent in mitigating the risk of raised ICP or secondary synostoses in the syndromic population.…”
Section: Icp and Need For Secondary Interventionmentioning
confidence: 99%
“…Since these surgeries are typically performed in the first 6 months of age, it is important to identify the optimal time to intervene for best surgical outcome while having the least detrimental impact to the patient (Yarbrough et al. ; Sivakumar et al. ; Bergquist et al.…”
Section: Introductionmentioning
confidence: 99%